Investigation of the Influence of UV-Irradiation on Thermal Stability of Binary Systems on the Basis of Polyethylene Glycol Fumarate with Some Vinyl Monomers - Burkeyeva, G.K.; Kovaleva, A.K.; Tazhbayev, Ye.M.; Ibrayeva, Zh.M.; Zhaparova, L.Zh.; Meiramova, D.R.; Plocek, J. (Eurasian Journal of Chemistry, 2023)
This work is devoted to the investigation of continuous exposure to UV-irradiation on thermal stability of polymeric base of sealants. The copolymers of polyethylene glycol fumarate with acrylic and methacrylic ac-ids, and acrylamide of the composition of “unsaturated polyester: vinyl monomer” ~35:65 mass.% (corre-spondingly) were chosen as the polymer base. The samples were analyzed on microscope to the presence of microcracks as a result of exposure to UV-irradiation on them. The studied samples were evaluated visually on color change and the appearance of turbidity. Thermal stability of the studied polymeric base was deter-mined by establishing the temperature of the start of thermal deformation by thermogravimetry before and af-ter the process of UV-irradiation within 21 days. It was established that for the polymeric base with acryla-mide in its content the temperature of the start of thermal deformation had reduced after exposure to UV-irradiation. In contrary, for the polymeric bases with acrylic and methacrylic acids in their composition the above said thermal index almost had not changed after affecting with UV-irradiation on the samples
Keywords: polymer base; sealants; UV-irradiation; thermal deformation; unsaturated polyesters; polyethylene glycol fumarate